The role of distractor inhibition in the attentional boost effect: evidence from the R/K paradigm. Issue 6 (3rd July 2019) - Meng, Yingfang; Lin, Guyang; Lin, Huiru
ABSTRACT: Stimuli presented with targets in a detection task are later recognised more accurately than those presented with distractors, an unusual effect labelled the attentional boost effect (ABE). This effect may reflect an enhancement triggered by target detection, the inhibition of distractor rejection, or some combination of both. To test these possibilities, the present study adopted a baseline similar to that of Swallow and Jiang ([2014b]. The attentional boost effect really is a boost: evidence from a new baseline. Attention, Perception, & Psychophysics, 76 (5), 1298–1307); the goal was to separate target-induced enhancements from distractor-induced inhibition. An R/K procedure was applied to further explore the kind of memory that might be affected by target detection or distractor rejection. The results show that the memory advantage for target-paired words was robust relative to that of baseline words; this advantage was mainly observed in R responses. More importantly, a memory reduction was also observed for distractor-paired words relative to baseline words, though this reduction was only observed in R responses. These data led us to conclude that the ABE was triggered by both processes: target-induced enhancement and distractor-induced inhibition. Moreover, both processes were more likely to affect recollection-based recognition.